Study of the Kinetics of Reduction of IrO2 on TiO2 (Anatase) by Temperature-Programmed Reduction - Shahad Batubara; Mogbel Alrushaid; Muhammad Amtiaz Nadeem; Hicham Idriss (Inorganics, 2023)
The interaction between IrO2 and TiO2 (anatase) in non-isothermal reduction conditions has been studied by the temperature programmed reduction technique. IrO2 clusters are of sizes between 0.5 and 0.9 nm as determined from High Resolution Transmission Electron Microscopy (HRTEM). Largely, two main regions for reduction were found and modeled at ca. 100 and 230 °C. The first region is attributed to the partial reduction of IrO2 clusters, while the second one is due to reduction of the formed crystalline (rutile IrO2), during TPR, to Ir metal. Two methods for calculating kinetic parameters were tested. First, by applying different ramping rates on a 3.5 wt.% IrO2/TiO2 using Kissinger’s method. The apparent activation energy values for the first and second reduction regions were found to be ca. 35 and 100 kJ/mol, respectively. The second method was based on fitting different kinetic models for the experimental results in order to extract qualitative information on the nature of interaction during the reduction process. It was found that the first reduction is largely due to the amount of IrO2 (reactant concentration) while the second one involved phase boundary effect as well as nucleation.